Development of E-Flipbook Based Learning Media to Improve Students Learning Outcomes in Natural and Social Learning in Fourth Grade Elementary School - Rossa Andriyani; Tri Astuti (FKIP - Universitas Riau, 2026)
The application of Natural and Social Sciences (IPAS) learning within the Independent Curriculum requires innovative instructional media to increase student engagement and improve learning outcomes. However, classroom practices still rely on textbooks and lecture-based methods, resulting in low participation and suboptimal achievement. This research aims to develop E-Flipbook learning media, examine its feasibility, and analyze its effectiveness in improving student learning outcomes. The study employed a Research and Development (R&D) approach based on the Borg and Gall model. Data were collected through expert validation, questionnaires, and learning achievement tests. The data were analyzed using a normality test, paired-samples t-test, and N-gain analysis. The results show that the E-Flipbook is highly feasible, with validation scores of 97% from material experts and 98% from media experts. Additionally, the paired-samples t-test indicated a significant improvement (p < 0.001), and N-gain results were in the moderate category. Therefore, the E-Flipbook is effective in enhancing student learning outcomes and supporting interactive learning processes.